Answer:
x=-1 and y=2
Explanation:
Given,
and
![2x=-y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ecq3k3vtb9w9r85rkkvujhi279yvukeenf.png)
Solution,
equation 1
![2x=-y\\y\ =-2x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mcyz6kgjtiydajhvsgtr9phwysrbv89pb9.png)
Now substituting the value of y in equation 1, we get;
![4x + (-2x) = -2\\4x-2x\ =-2\\2x=-2\\x=-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/itccpn6fv4kp36672u92ohqao32lzvqy1y.png)
Now
![y =-2x = -2*-1=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bzzecoeiysp3jszjighwkm6ft1v9wyi7r8.png)
So the solution of the given equation is x=-1 and y=2
Check:
Substituting the value of x and y in equation 1 we get;
![4x + y = -2\\4*-1+2=-2\\-4+2=-2\\-2=-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ktke8gh758m4emtv06z17y1tb1ottrwjc8.png)
L.H.S=R.H.S
Substituting the value of x and y in equation 2 we get;
![2x=-y\\2*-1= -2\\-2=-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bg7r8kuvwzmfd2pdwb20gnm5p0egihg7d9.png)
L.H.S=R.H.S